2014
DOI: 10.5455/medarh.2014.68.350-352
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rehabilitation Protocol on Functional Recovery After Anterior Cruciate Ligament Reconstruction

Abstract: Introduction:The use of rehabilitation protocol which corresponds to surgical technique results in optimal postoperative outcome and functional recovery of patients to a pre-injury level of activity. The aim of this paper is to show the effects of the official rehabilitation protocol in our Institute on functional recovery of patients after anterior cruciate ligament (ACL) reconstruction.Patients and methods:In prospective study, we evaluated 70 males after ACL reconstruction using hamstring graft. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(12 reference statements)
2
10
0
5
Order By: Relevance
“…They both found no between-group differences in ROM, quadriceps and HS strength and hop tests at >1 year follow-up,56 57 but Grant and Mohtadi56 found a better self-reported knee function in the home-based group. The level C prospective cohort study of Dragicevic-Cvjetkovic et al 58 found a better self-reported knee function and greater improvement in thigh muscle circumference in a rehabilitation group (20 weeks) compared to a group with no rehabilitation at all at a 1 year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…They both found no between-group differences in ROM, quadriceps and HS strength and hop tests at >1 year follow-up,56 57 but Grant and Mohtadi56 found a better self-reported knee function in the home-based group. The level C prospective cohort study of Dragicevic-Cvjetkovic et al 58 found a better self-reported knee function and greater improvement in thigh muscle circumference in a rehabilitation group (20 weeks) compared to a group with no rehabilitation at all at a 1 year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Massages allowed lymphatic drainage and decreased edema. Finally, the Lysholm-Tegner, IKDC, and KOOS questionnaires showed an increase in scores between preoperative evaluation and evaluation 6 months after surgery in both rehabilitation groups ( 41 ). Thus, patients judged the functionality of their knee to be better 6 months after surgery than before surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Cvjetkovic, et al [ 46 ], in their prospective study of 70 males, examined the effect of a rehabilitation program on thigh muscle circumference and modified Tegner Lysholm score. Patients were divided into two groups each of 35 patients.…”
Section: Reviewmentioning
confidence: 99%